Respuesta :

Answer:

The value of given expression is 3.

Step-by-step explanation:

The given expression is

[tex]27+(-24)[/tex]

According to the rule of addition and subtraction,

[tex](+)\cdot (-)=(-)[/tex]

It means,

[tex]a+(-b)=a-b[/tex]

By using this rule we get,

[tex]27+(-24)=27-24[/tex]

[tex]27+(-24)=3[/tex]

Therefore the value of given expression is 3.

Answer:

The answer is 3

Step-by-step explanation:

27 can be re-written as 3+24. Now, the expression can be re-written as 3+24+(-24) = 3+24-24 = 3+0 =3. The key thing to keep in mind here is that +(-) = -